The Influence of Flexible Work Arrangements on Employee Innovation Moderated by Human Resource Support in the Information Technology and Telecommunications Industry: A Mixed-Methods Approach - Julianne Cu, Akisha; Nikole Esguerra, Zoraia; Gatbonton, Angela; Sakhrani, Janvi; Ranieses, Jessica Jaye (SEISENSE Journal of Management, 2025)
Purpose- This study, grounded in the Demand–Resource–Individual Effects (DRIVE) Model and Social Exchange Theory (SET), explores the impact of Flexible Work Arrangements (FWAs)—namely Flexible Working Hours (FWH) and Telecommuting/Work From Home (T/WFH)—on Employee Innovation (EI), with an examination of Human Resource Support (HRS) as a potential moderating factor.Design/Methodology- Utilizing a mixed-methods design, this research integrates quantitative results from 150 purposively and snowball-sampled respondents with qualitative insights from four detailed interviews. Statistical analyses included Correlation, Regression, and Explanatory Sequential analysis.Findings- The study’s key findings show that both FWH and T/WFH significantly enhance EI. While quantitative findings indicated no significant moderating effects of HRS, qualitative responses underscored its vital role in fostering a supportive and innovative environment. Practical Implications- These findings underscore the crucial role of FWAs in enhancing innovation and suggest that fostering schedule autonomy and strengthening support systems can significantly boost innovation in hybrid work setups.